Current State of Anthrax Vaccines and Key R&D Gaps Moving Forward - Adam Clark; Daniel N. Wolfe (Microorganisms, 2020)
A licensed anthrax vaccine has been available for pre-exposure prophylaxis in the United States since 1970, and it was approved for use as a post-exposure prophylaxis, in combination with antibiotic treatment, in 2015. A variety of other vaccines are available in other nations, approved under various regulatory frameworks. However, investments in anthrax vaccines continue due to the severity of the threat posed by this bacterium, as both a naturally occurring pathogen and the potential for use as a bioweapon. In this review, we will capture the current landscape of anthrax vaccine development, focusing on those lead candidates in clinical development. Although approved products are available, a robust pipeline of candidate vaccines are still in development to try to address some of the key research gaps in the anthrax vaccine field. We will then highlight some of the most pressing needs in terms of anthrax vaccine research.